HUBUNGAN KONSUMSI TABLET FE DENGAN KEJADIAN ANEMIA DI PUSKESMAS PENRANG KABUPATEN WAJO - Yenni Yenni; Andi Tenri Angka (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2020)
Iron (Fe) tablets are mineral tablets that the body uses to make red blood cells and hemoglobin. For red blood cell production, Fe is the most significant element. Food is a natural source of iron. Nutritional anemia can develop in pregnant women if they don't get enough iron in their diet (blood deficiency). Pregnant women need iron (Fe) tablets, so they must consume at least 90 Fe tablets during pregnancy. The aim of the research was to determine the relationship between consumption of Fe tablets and the incidence of anemia at the Penrang Community Health Center, Wajo Regency. The type of research used was a cross sectional study. The samples were 72 pregnant women who underwent pregnancy checks at the Penrang Community Health Center, Wajo Regency, using a random sampling technique. The research results showed a relationship between consumption of Fe tablets and the incidence of anemia at the Penrang Health Center, Wajo Regency, where the p value = 0.000 < ? = 0.05. The conclusion is that there is a relationship between the consumption of Fe tablets and the incidence of anemia at the Penrang Community Health Center, Wajo Regency.